Symposium 6: The place of technology in networked learning: Symposium Introduction - Jones, Chris (Proceedings of the International Conference on Networked Learning, 2012)
This symposium brings together three papers focused around the theme of technology and its relationship to networked learning. The definition of networked learning that has informed the conference series has always contained the notion that networked learning is related to the use of technology. Networked learning is "learning in which information and communication technology…is used to promote connections: between one learner and other learners, between learners and tutors; between a learning community and its learning resources" (Goodyear et al., 2004, p1). This symposium is concerned with how to understand that relationship between digital and networked technologies and networked learning.